Adult education in the American experience : - Stubblefield, Harold W. (Jossey-Bass Publishers, 1994)
From the earliest contributions of Native Americans in the colonial period to the workforce preparation crisis in the 1980s, this book explores the patterns, themes, and changing ideologies of learning and education in adulthood.